2021
DOI: 10.1080/00365521.2021.1953129
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of prophylactic clip closure of mucosal defects after colorectal endoscopic submucosal dissection on delayed bleeding

Abstract: Objective: Although prophylactic clip closure after endoscopic mucosal resection may prevent delayed bleeding, information regarding colorectal endoscopic submucosal dissection (CR-ESD) is lacking. Therefore, this study evaluated the effect of prophylactic clip closure on delayed bleeding rate after CR-ESD. Materials and methods: A total of 614 CR-ESD procedures performed in 561 patients were retrospectively reviewed. The primary outcome, which was delayed bleeding rate, was analyzed between the prophylactic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…5). 54,65,[77][78][79][80][81] Several meta-analyses have revealed the effectiveness of endoscopic closure to prevent postpolypectomy DB, [73][74][75] concluding that closure contributes to DB reduction for >20 mm proximal colorectal polyps. The authors considered that a thinner wall and more superficial submucosal arteries in the proximal than distal colon may lead to an increased bleeding risk after polypectomy-induced submucosal vessel coagulation injury.…”
Section: Incidence Of and Risk Factors For Aes After Colorectal Esdmentioning
confidence: 99%
See 3 more Smart Citations
“…5). 54,65,[77][78][79][80][81] Several meta-analyses have revealed the effectiveness of endoscopic closure to prevent postpolypectomy DB, [73][74][75] concluding that closure contributes to DB reduction for >20 mm proximal colorectal polyps. The authors considered that a thinner wall and more superficial submucosal arteries in the proximal than distal colon may lead to an increased bleeding risk after polypectomy-induced submucosal vessel coagulation injury.…”
Section: Incidence Of and Risk Factors For Aes After Colorectal Esdmentioning
confidence: 99%
“…76 Several studies have revealed the efficacy of colorectal post-ESD defect closure to reduce the risk of AEs. 54,70,[77][78][79]81 Because most of these studies were retrospective, selection bias cannot be avoided. Two RCTs showed negative results of defect closure to reduce DB, 65,80 whereas a recent meta-analysis clarified the efficiency of defect closure for preventing AEs after colorectal ESD (OR 0.19; 95% CI 0.08-0.49; P = 0.0005).…”
Section: Incidence Of and Risk Factors For Aes After Colorectal Esdmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent randomized controlled trial (RCT) [18] and several meta-analyses [19][20][21] revealed that prophylactic closure after polypectomy reduces DB in the right side of the colon. Furthermore, several retrospective studies [12,22] and a meta-analysis [23] showed the efficacy of prophylactic closure in preventing DB after colorectal ESD. The need for prophylactic closure may be influenced by the procedural differences between polypectomy and ESD because of the differences in the density and thickness of the vessels in the dissected layer.…”
Section: Discussionmentioning
confidence: 99%